Blockchain-Based Credentialing for Teachers: A Systematic Literature Review on Transparency and Trust in Educational Management - Marnita, Marnita; Safarati, Nanda; Bensaadi, Iswadi; Taufiq, M. (CV Raskha Media Group, 2025)
This study presents a systematic literature review (SLR) of blockchain applications in educational credentialing, with a particular emphasis on teacher professional development and governance. While most existing research focuses on higher education credentials, this review highlights the limited exploration of blockchain in teacher credentialing, despite its significant potential to address persistent challenges such as credential fraud, data fragmentation, and slow verification processes. Guided by the PRISMA 2020 framework, the review synthesizes 27 peer-reviewed studies published between 2019 and 2025. The findings reveal that blockchain’s core features —immutability, verifiability, and decentralization —can transform credential governance from a “trust-by-institution” model to a “trust-by-design” system. This paradigm shift enables tamper-resistant records, cross-institutional verification, and transparent audit trails, thereby enhancing accountability. The study makes three key contributions. Theoretically, it extends the literature by systematically consolidating knowledge on the role of blockchain in teacher credentialing, offering a novel perspective on its governance implications. Practically, it provides concrete recommendations for policymakers, institutions, teachers, and technology developers, with relevance for developing countries. In the Indonesian context, blockchain integration with systems such as SIMPKB, SISTER, and PDDikti is proposed as a pathway toward more transparent, accountable, and competency-based teacher management. Finally, the review identifies future research directions, including empirical pilot studies, cross-country comparisons, ethical frameworks for data privacy, and cost-benefit analyses of adoption in resource-constrained settings. Overall, this study highlights blockchain not only as a technological innovation but also as a governance strategy that can strengthen trust, accountability, and transparency in teacher credentialing systems.